Enchantment in the Garden - Hughes, Shirley (Random House UK Ltd, 1998)
This is the tale of a lonely young girl's magical friendship with the marble statue of a boy which comes to life, and whose friendship has a lasting impact upon her.
Keywords: Juvenile literature-Fiction